Temporal evolution of long-lived magmatic systems: the Chachani volcano complex, south of Perù - Aguilar Contreras, Rigoberto (2018)
The Chachani Volcanic Complex (CVC) is an extensive (~289±10 km3) assemblage of spatially, temporally and genetically related major and minor eruptive centers. The c. 1.2 Myr-long activity suggests that the CVC is a long-lived volcanic system characterized by semi-persistent activity and short periods of quiescence. The stratigraphy, Ar/Ar and U/Pb chronology, spatial distribution along lineaments, and the degree of landform preservation help distinguish two groups of edifices in the CVC. The ‘old’ edifice group is characterized by large stratovolcanoes and small dome coulees. This group has been built between.